Social - Fernandes, Ionara dos Santos; Simas, Fábio do Nascimento; Dias, João Rafael da Conceição (Argumentum, 2025)
This article problematises the relationship between Brazilian Social Work and the national policy for preventing and combating torture. With an emphasis on the deprivation of liberty, it discusses historical and political aspects of torture in Brazil and its confrontation by means of professional action. This is qualitative research drawn from bibliographical study and documentary analysis of reports produced by the first team responsible for the national policy for the prevention and combating of torture. It concludes that academic output on the topic of torture in Social Work is scarce. Political and professional intervention strategies for the category are also highlighted.